1988
DOI: 10.1152/ajpcell.1988.254.4.c491
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine suppresses length dependency of Ca2+ sensitivity of skinned striated muscle

Abstract: Freeze-dried skinned cardiac and skeletal muscle preparations of the rabbit were immersed in Ca2+-containing solutions with different concentrations of caffeine. The relation between the negative logarithm of the Ca2+ concentration (pCa) and normalized developed force was studied. The exact position of these Ca2+-sensitivity functions proved to be dependent on both the sarcomere length (monitored by means of laser diffraction) and caffeine concentration. High concentrations of caffeine induce a reversible fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…There are two possible explanations for this difference with the present results. (i) The effects of caffeine on Ca2" sensitivity have been reported to be enhanced at short sarcomere lengths (De Beer et al 1988). This could explain the prominent maintained contracture seen in the present unloaded contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible explanations for this difference with the present results. (i) The effects of caffeine on Ca2" sensitivity have been reported to be enhanced at short sarcomere lengths (De Beer et al 1988). This could explain the prominent maintained contracture seen in the present unloaded contractions.…”
Section: Discussionmentioning
confidence: 99%
“…). Furthermore we have taken no account of the observation that the effects of caffeine depend on sarcomere length(De Beer et al 1988) and will therefore change during the contracture.…”
mentioning
confidence: 99%
“…Even less is known about how caffeine suppresses maximum force. One possibility is that it is due to an increase in myofilament lattice spacing (de Beer et al 1988). It would seem that the depression of force is not related to Ca2+ sensitization, since some Ca2+ sensitizing agents such as sulmazole enhance maximum force (Lamont & Miller, 1992); in addition, force and Ca2" sensitivity were affected differentially, in that caffeine reduced maximum force similarly in the two muscle types (Fig.…”
Section: Maximum Force Production In Skinned Fibresmentioning
confidence: 96%
“…The rise in pCa50 induced by caffeine was three times greater for trabeculae (0-31 + 0 04, n = 5) than for skeletal fibres (0 09 + 0 01, n = 4). To see whether this difference was due to the longer SL in the psoas fibres, since it has been reported that the Ca2" sensitization by caffeine is less at longer SL (de Beer, Grundemann, Wilhelm, Caljouw, Klepper & Schiereck, 1988), in separate 20 - experiments we varied the SL in skeletal fibres over a wide range (1P6-2-8 ,um). However, the increase in pCa50 induced by caffeine in psoas muscles was found to be independent of SL (results not shown), suggesting that the greater Ca2+sensitizing action of caffeine in cardiac fibres compared with skeletal fast-twitch fibres was due to a true difference between muscle types.…”
Section: Caffeinementioning
confidence: 99%
“…A set-up similar to that described by De Beer et al (1988) was used to monitor tension development in the labelled muscle fibres. The fibres were mounted between two stainless steel clips, one of which was attached to a strain gauge force transducer (AME 801, Aksjeselskapet Mikro Elektronikk).…”
Section: Tension Development Of Labelled Muscle Fibresmentioning
confidence: 99%